Self-healing of modified sulfur composites with calcium sulfoaluminate cement and superabsorbent polymer. (1st April 2019) - Gwon, Seongwoo; Ahn, Eunjong; Shin, Myoungsu
Abstract: This study investigated the applicability of calcium sulfoaluminate (CSA)-based cement and superabsorbent polymer (SAP) to the self-healing of modified sulfur composites. Modified sulfur was used as a binder in the sulfur composites. Eight different mixtures were tested by varying the ratio between CSA expansive agent and Portland cement in the CSA-based binary cement, with or without the addition of SAP. A series of nondestructive evaluation analyses, including optical microscopy, computed tomography, and elastic wave transmission, confirmed the synergetic effect of the CSA cement and SAP on the self-healing of modified sulfur composites in wet environments. Both the CSA cement and SAP remained intact in the hardened sulfur composites, but after crack generation and water infiltration, hydrated cement phases and/or swollen SAP particles were produced in the crack gap. The crack-sealing progressed faster and tighter as the portion of CSA expansive agent increased in the binary cement. In addition, the use of SAP greatly escalated the self-healing performance. The reaction products newly formed in the crack gap reflected the self-healing mechanism of the sulfur composites.